2012
DOI: 10.1007/s13361-012-0413-z
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Assisted Ionization: New Aromatic and Nonaromatic Matrix Compounds Producing Multiply Charged Lipid, Peptide, and Protein Ions in the Positive and Negative Mode Observed Directly from Surfaces

Abstract: Matrix assisted inlet ionization (MAII) is a method in which a matrix:analyte mixture produces mass spectra nearly identical to electrospray ionization without the application of a voltage or the use of a laser as is required in laserspray ionization (LSI), a subset of MAII. In MAII, the sample is introduced by, for example, tapping particles of dried matrix:analyte into the inlet of the mass spectrometer and, therefore, permits the study of conditions pertinent to the formation of multiply charged ions withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
213
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 62 publications
(226 citation statements)
references
References 120 publications
12
213
1
Order By: Relevance
“…Recently, it has been shown that solid matrices produce almost identical charge state ions when introduced to the inlet of an atmospheric pressure ionization mass spectrometer [7,29]. Unlike ESI and SAII, 3-NBN acts as a matrix producing analyte ions near room temperature where it is a solid [30,31]. Assuming charged particles are intermediates in all processes that produce highly charged ions, it is not obvious how the charged solid particles can produce ions of similar charge state to liquid droplets.…”
Section: Survival Yield With Matrix-assisted Ionizationmentioning
confidence: 99%
“…Recently, it has been shown that solid matrices produce almost identical charge state ions when introduced to the inlet of an atmospheric pressure ionization mass spectrometer [7,29]. Unlike ESI and SAII, 3-NBN acts as a matrix producing analyte ions near room temperature where it is a solid [30,31]. Assuming charged particles are intermediates in all processes that produce highly charged ions, it is not obvious how the charged solid particles can produce ions of similar charge state to liquid droplets.…”
Section: Survival Yield With Matrix-assisted Ionizationmentioning
confidence: 99%
“…I-B), which operates independent of a voltage or a laser ( 56 ). MAII and LSII depend on the appropriate matrix (57)(58)(59), similar to MALDI ( 60-63 ), but do not require absorption at the laser wavelength employed. In LSII, the laser ablation only acts as the method to transfer a matrix/analyte sample into the inlet of the mass spectrometer, permitting the use of highly focused lasers to improve spatial resolution.…”
Section: Laserspray Ionization Inlet (Lsii) Is a Novel Methods (Supplementioning
confidence: 99%
“…Approximately 20 laser shots were summed for each spectrum. LSII-MS was performed on the SYNAPT G2 by converting the nano-ESI source to a LSII source according to published procedure (54)(55)(56)(57)(58)(59)68 ) using the 337 nm nitrogen laser employed for LSII-MS on the LTQ Velos.…”
Section: Laserspray Ionization Inlet (Lsii) Is a Novel Methods (Supplementioning
confidence: 99%
See 2 more Smart Citations